Patient-reported intestinal toxicity from whole pelvis intensity-modulated radiotherapy: First quantification of bowel dose–volume effects. Issue 2 (August 2017) - Sini, Carla; Noris Chiorda, Barbara; Gabriele, Pietro; Sanguineti, Giuseppe; Morlino, Sara; Badenchini, Fabio; Cante, Domenico; Carillo, Viviana; Gaetano, Marcella; Giandini, Tommaso; Landoni, Valeria; Maggio, Angelo; et al.
Abstract: Background and purpose: Intestinal toxicity is commonly experienced during whole-pelvis intensity-modulated radiotherapy (WPRT) for prostate cancer. The aim of the current study was to assess bowel dose–volume relationships for acute patient-reported intestinal symptoms of patients treated with WPRT for prostate cancer. Materials and methods: Complete data of 206 patients were available; the median dose to pelvic nodes was 51.8 Gy (range 50.4–54.4, 1.7–2 Gy/fr). Intestinal symptoms were assessed as changes in the Inflammatory Bowel Disease Questionnaire scores relative to the Bowel Domain (IBDQ-B) between baseline and radiotherapy mid-point/end. The 25th percentiles of the most severe worsening from baseline (ΔIBDQ-B) were set as end-points. The impact of bowel loops and sigmoid colon dose–volume/surface parameters as well as selected clinical parameters were investigated using multivariate logistic regression. Results: Analyses were focused on the four questions showing a median ΔIBDQ-B > 0. No dose volume/surface parameters were predictive, other than ΔIBDQ5 ≥ 3 (loose stools): when grouping patients according to bowel DVHs (high risk: V20 > 470 cc, V30 > 245 cc, V42 > 110 cc; low risk: all the remaining patients), a two-variable model including high-risk DVH-shape (OR: 9.3) and age (protective, OR: 0.94) was assessed. The model showed good calibration (slope: 1.003, R 2  = 0.92) and was found to be robust after bootstrap-based internal validation. Conclusions: Constraining the bowel loops may reduce the risk of loose stools. The risk is higher for younger patients.